The effect of transformational entrepreneurship on competitive advantage in tourism and hospitality organizations through organizational support and employee resilience - Ahmed, Hebatallah A. M.; Al-Romeedy, Bassam Samir; Badwy, Hanan Eid; Abdelghani, Abdelrahman A. A. (Research Journal in Advanced Humanities, 2025)
This study investigates the effect of transformational entrepreneurship on competitive advantage in tourism and hospitality organizations, with a focus on the mediating roles of organizational support and employee resilience. Drawing on data from 421 employees across Egyptian travel agencies, the research employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to test hypothesized relationships. Results reveal that transformational entrepreneurship positively influences competitive advantage (β = 0.16, p < 0.01), organizational support (β = 0.66, p < 0.01), and employee resilience (β = 0.66, p < 0.01). Organizational support (β = 0.27, p < 0.01) and employee resilience (β = 0.45, p < 0.01) further exert significant direct effects on competitive advantage. Mediation analysis confirms that both organizational support (β = 0.178, p < 0.01) and employee resilience (β = 0.297, p < 0.01) partially mediate the relationship between transformational entrepreneurship and competitive advantage. These findings underscore the importance of integrating transformational leadership, robust support systems, and resilience-building initiatives to foster sustainable competitive differentiation in dynamic markets. The study advances theoretical frameworks by linking transformational entrepreneurship to resource-based and dynamic capabilities theories, while offering practical insights for enhancing organizational agility and workforce adaptability in the tourism and hospitality sector.